The COVID-19 and tourism in Peru. Analysis and proposals towards a new scenario - Paredes Izquierdo, Juan Carlos (2020)
The COVID-19 pandemic has generated a global crisis that has impacted all human activities. One of the hardest hit is tourism which, by its very nature, faces the difficult and unavoidable challenge of creating the conditions to ensure, as far as possible, the health of tourists, generating in them the confidence necessary for a gradual return to activity. This article addresses this issue from an analysis of the current situation of tourism in Peru, to a set of proposals for its reactivation, both at a general level and in certain key subsectors.